Four decades of the Graf method in screening for developmental dysplasia of the hip (part I): Rightly the gold standard or of dubious benefit? - Robert Ossendorff; Sonja Placzek; Rahel Bornemann; Sebastian G. Walter (Frontiers Media S.A., 2022)
IntroductionThe method of infant hip sonography according to Graf is used for general hip screening in Serbia, Austria, and Germany and is considered the gold standard. In other countries, such as the USA, however, it is not well accepted and is claimed to lead to high costs and overtreatment. The aim of this study was to investigate how many of the mentioned sources in a recent review article contained sonograms that met the quality criteria as taught in Graf's ultrasound courses.MethodsA systematic review published by Sakkers et al. was analyzed in terms of addressing the quality criteria of Graf's method. Studies that were suitable by title, abstract, manuscript, that contained an image of sonographic hip examination, and that were accessible were included into analysis.ResultsWithin the described review, there were 22 papers on the Graf method. Of these, 10 contained hip sonograms and were applicable for final analysis. The quality criteria according to Graf were not fulfilled within 5 of these 10 papers. Within these papers, there are examples of schematic sonograms that do not correspond with the quality criteria either.ConclusionSkepticism regarding the Graf method may be based on user errors and insufficient application of the Graf quality assessment algorithm, which results in high intra- and inter-observer variations. Based on these findings, a working group was initiated to evaluate further work according to the same procedure (currently approximately 130 papers).